Microstructure formation of silicide coating on Nb–W–Mo–Zr alloy. (3rd July 2019) - Qiao, Yanqiang; Zheng, Kewei; Guo, Xiping
ABSTRACT: Silicide coatings were deposited on the Nb–5W–2.5Mo–1Zr alloy by pack cementation method. The microstructure, phase distribution, growth kinetics and oxidation behaviour of the coatings were studied. The results show that the coatings were mainly composed of an outer NbSi2 layer, an acicular Nb5 Si3 -dispersed NbSi2 two-phase layer and a Nb5 Si3 inner layer, exhibiting a three-layer structure. The temperature and holding time both have a significant effect on the coating formation. It was found that the coating growth kinetics at 1250°C followed a parabolic law. The coating exhibited a relatively good short-term protection to the substrate in static air at 850 and 1250°C. Both scales formed at the two oxidation temperatures consisted mainly of a mixture of SiO2, Nb2 O5 and NbO.